2003
DOI: 10.1177/002215540305100312
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of Rat Growth Plates: Cessation of Growth with Age Despite Presence of a Physis

Abstract: Despite the continued presence of growth plates in aged rats, longitudinal growth no longer occurs. The aims of this study were to understand the reasons for the cessation of growth. We studied the growth plates of femurs and tibiae in Wistar rats aged 62-80 weeks and compared these with the corresponding growth plates from rats aged 2-16 weeks. During skeletal growth, the heights of the plates, especially that of the hypertrophic zone, reflected the rate of bone growth. During the period of decelerating growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
143
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(151 citation statements)
references
References 46 publications
7
143
0
1
Order By: Relevance
“…In some species, the epiphysis may remain ''open'' for some time beyond the achievement of sexual maturity (Kilborn et al, 2002). As previously demonstrated in rats by both Trudel et al (2001) and Roach et al (2003) and others, we observed histologically 'open' physes in rats at 1 year of age. In departure from the former and in agreement with the latter study, we measured no significant proliferative activity or daily growth accumulation by the proximal tibial growth plate by our pulse labeling studies at this late time point.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…In some species, the epiphysis may remain ''open'' for some time beyond the achievement of sexual maturity (Kilborn et al, 2002). As previously demonstrated in rats by both Trudel et al (2001) and Roach et al (2003) and others, we observed histologically 'open' physes in rats at 1 year of age. In departure from the former and in agreement with the latter study, we measured no significant proliferative activity or daily growth accumulation by the proximal tibial growth plate by our pulse labeling studies at this late time point.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…Endochondral bone formation in mice differs from that in humans, as their growth plates do not fuse completely during sexual maturation (Roach et al 2003). Therefore, it can be argued that estrogen receptors in mice, unlike those in humans, do not mediate growth plate fusion (Lubahn et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in humans, the growth plates in mice do not fuse completely during sexual maturation (Roach et al 2003). However, their height diminishes considerably after sexual maturation, and the protein synthesis rate in the chondrocytes decreases.…”
Section: Introductionmentioning
confidence: 86%
“…In rats, the growth plate remains present in aged rats despite the absence of longitudinal growth 13 . For this reason the growth plate was radiographically visible at all moments in both groups from both craniocaudal and mediolateral views.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, differences in the bone length on day 21 were observed especially in G1 as compared to G2, suggesting a negative effect of LLLT on growth plate proportional to the number of irradiation days. In addition, the rats were approximately 6 weeks of age on the first day of irradiation, a transitional period between a phase of accelerating growth (up to 5 weeks) and a time of decelerating growth (8-16 weeks) 13 , indicating that irradiation action occurs despite the longitudinal length rate of the bone.…”
Section: Discussionmentioning
confidence: 99%